Pengaruh Literasi Keuangan dan Financial Technology (Fintech) Terhadap Prilaku Keuangan pada UMKM di Kecamatan Kayuagung - Muhammad Rezha Damargalih Tanjung; Dewi Sartika (Masyarakat Ekonomi Syariah Bogor, 2025)
This research evaluates the influence of financial literacy and the use of financial technology (Fintech) on the financial behavior of MSMEs in Kayuagung District. Data was collected through a survey of 100 MSME respondents using a Likert-based questionnaire. The results of the analysis show that financial literacy has a significant influence on financial behavior, especially in financial planning, debt management and investment. Apart from that, financial literacy also has a significant influence on Fintech adoption, which increases the efficiency of financial management and access to financial services. The use of Fintech itself has a positive impact on the financial behavior of MSMEs, with Fintech strengthening the relationship between financial literacy and financial behavior.